Dynamic Capabilities in Public Health Organizations: Literature Review - Ruben LOUREIRO; António CARDOSO; Jorge SIMÕES (Communications of International Proceedings, 2021)
Strategic Management represents a field of multidisciplinary research that has evolved rapidly with various theories and approaches in recent decades. It was the criticisms of the Theory of Resources and Capabilities that led Teece and Pisano (1994) to present the perspective of Dynamic Capabilities (CD), becoming one of the most notorious approaches in the field of strategic management, however, still difficult to measure and operationalize today from a practical point of view and with great weakness in terms of theoretical conceptualization. In all sectors, public or private, the current context of organizations is characterized by technological, economic, political, social and cultural changes, which affect relations between countries and companies. In the public sector, the political factor and its cycles are present in a higher dimension, as well as social and human responsibility in the area of health, allowing us to differentiate our study environment from all the others. In this environment of constant change, we can consider that all public sector Health Organizations feel, on a daily basis, the need to innovate and respond to demand, with increasingly differentiated technology and the need to position themselves in the market, improving the market perspective. in relation to the service provided. The DCs are renewed in order to respond to changes in the environment, and organizations must assemble capacities to sustain a good performance. In this segment, DCs have an essential role in the performance of organizations. Several studies report the inefficiency of the health system, not only at the national level but in many of the more developed countries, causing a sharp increase in health costs.
Keywords: Dynamic Capabilities; Resources; Strategic Management; Public Health Organizations.